The Economy: Treading on Thin Ice Perception or Reality? - Lachance, Laurie (Maine Policy Review, 2001)
Although the past nine years have been ones of tremendous growth for both the U.S. and Maine economies, today the economy shows signs of weakening. Consumer confidence has taken a nosedive; recent stock market activity has been sluggish; and, nominal oil prices since 1999 have nearly tripled. Moreover, Maine has its own set of cautionary signs: the multiple job-holding rate in Maine is 25 percent higher than it is in the United States; bankruptcy filings remain alarmingly high—as do personal debt levels. In this “status of the economy” article, State Economist Laurie Lachance discusses these trends and the implications they may hold for Maine’s future. Despite today’s warning signals, she concludes that, on balance, the outlook for the future is decent. In short, perhaps what we face is vulnerability, not disaster.